Prevention paradox logic and problem gambling: Does low-risk gambling impose a greater burden of harm than high-risk gambling? - Delfabbro, Paul (J Behav Addict, 2017)
BACKGROUND AND AIMS: The aim of this paper is to examine the evidence and arguments in favor of prevention paradox (PP) logic in the context of problem gambling. Evidence from recent studies of gambling and the distribution of harm across lower and higher risk gamblers is reviewed to examine the contention that the absolute burden of harm is greater in low-risk (LR) gamblers than the problem gamblers. METHODS: The review examines a number of methodological and conceptual concerns about existing evidence in support of the PP. RESULTS: The principal problems identified include the misclassification of LR gamblers; the use of binary scoring method that understates the frequency of harms in high-risk populations; a tendency to confuse behavior and harm; and the use of potentially overly inclusive definitions of harm with low thresholds of severity. DISCUSSION AND CONCLUSIONS: This paper makes a number of recommendations for enhancement of this area of research, including the use of clear definitions of harm and LR behavior and a greater focus on harm with material impacts on people’s quality of life.